Palmitoylethanolamide, a naturally occurring lipid, is an orally effective intestinal anti-inflammatory agent - Borrelli, Francesca (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: Palmitoylethanolamide (PEA) acts via several targets, including cannabinoid CB(1) and CB(2) receptors, transient receptor potential vanilloid type-1 (TRPV1) ion channels, peroxisome proliferator-activated receptor alpha (PPAR α) and orphan G protein-coupled receptor 55 (GRR55), all involved in the control of intestinal inflammation. Here, we investigated the effect of PEA in a murine model of colitis. EXPERIMENTAL APPROACH: Colitis was induced in mice by intracolonic administration of dinitrobenzenesulfonic acid (DNBS). Inflammation was assessed by evaluating inflammatory markers/parameters and by histology; intestinal permeability by a fluorescent method; colonic cell proliferation by immunohistochemistry; PEA and endocannabinoid levels by liquid chromatography mass spectrometry; receptor and enzyme mRNA expression by quantitative RT-PCR. KEY RESULTS: DNBS administration caused inflammatory damage, increased colonic levels of PEA and endocannabinoids, down-regulation of mRNA for TRPV1 and GPR55 but no changes in mRNA for CB(1), CB(2) and PPARα. Exogenous PEA (i.p. and/or p.o., 1 mg·kg(−1)) attenuated inflammation and intestinal permeability, stimulated colonic cell proliferation, and increased colonic TRPV1 and CB(1) receptor expression. The anti-inflammatory effect of PEA was attenuated or abolished by CB(2) receptor, GPR55 or PPARα antagonists and further increased by the TRPV1 antagonist capsazepine. CONCLUSIONS AND IMPLICATIONS: PEA improves murine experimental colitis, the effect being mediated by CB(2) receptors, GPR55 and PPARα, and modulated by TRPV1 channels.